2010
DOI: 10.1136/bjo.2008.145565
|View full text |Cite
|
Sign up to set email alerts
|

Transscleral diode laser cycloablation in patients with good vision

Abstract: In cases experiencing a 2 line loss in acuity, the main causes were glaucoma progression (9 cases) and macula oedema (4 cases). Visual loss was unrelated to total treatment dose (mean 99.7J), initial acuity or initial IOP level. IOP was controlled at final follow-up in 39/49 (79.6%) with no cases of hypotony. 3Conclusions: The majority of these eyes with difficult to manage glaucoma retained their good visual acuity over long-term follow-up after undergoing diode laser cyclophotocoagulation. The proportion los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
69
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 12 publications
9
69
1
3
Order By: Relevance
“…The MD values in our patients remained virtually unchanged after cyclodiode treatment from −8.74 dB preoperatively to −9.05 dB postoperatively. Previously, it has been reported that the most frequent cause of visual loss was further progression of glaucoma, which was an attributable cause in over half of the cases 22. The peri-operative visual field assessment presented in this study suggests that the maintenance of VA observed in the majority of the patients following cyclodiode treatment could be due to a good postoperative IOP control.…”
Section: Discussionsupporting
confidence: 50%
“…The MD values in our patients remained virtually unchanged after cyclodiode treatment from −8.74 dB preoperatively to −9.05 dB postoperatively. Previously, it has been reported that the most frequent cause of visual loss was further progression of glaucoma, which was an attributable cause in over half of the cases 22. The peri-operative visual field assessment presented in this study suggests that the maintenance of VA observed in the majority of the patients following cyclodiode treatment could be due to a good postoperative IOP control.…”
Section: Discussionsupporting
confidence: 50%
“…While traditionally reserved for eyes with poor visual potential, good outcomes have been reported with transscleral diode laser cycloablation in eyes with good vision 14. According to a recent survey, 60% of ophthalmologists would perform cyclodiode laser at any level of visual acuity 15.…”
Section: Discussionmentioning
confidence: 99%
“…During the same 10 years, rates of laser cycloablation to the ciliary body more than doubled in the over 60 s age group while remaining low in younger age groups (figure 3). Initially reserved for refractory IOP in eyes with poor vision, transscleral diode laser has potential for adverse effects on visual functioning 20 22 23. More recent reports have reported efficacy in patients with good visual acuity, therefore widening its acceptance and gaining support for its earlier use in those with less advanced glaucoma and better visual potential 22 23.…”
Section: Discussionmentioning
confidence: 99%
“…Initially reserved for refractory IOP in eyes with poor vision, transscleral diode laser has potential for adverse effects on visual functioning 20 22 23. More recent reports have reported efficacy in patients with good visual acuity, therefore widening its acceptance and gaining support for its earlier use in those with less advanced glaucoma and better visual potential 22 23. A recent British survey on transscleral diode photocoagulation revealed 60% of consultants perform cyclodiode at any level of visual acuity with only 12% reserving it for vision of 6/60 or worse 24.…”
Section: Discussionmentioning
confidence: 99%